EEF1A2 exacerbated insulin resistance in male skeletal muscle via PKCβ and ER stress. Issue 1 (January 2020) - Guo, Meng; Li, Yuna; Wang, Yan; Li, Zhenkun; Li, Xiaohong; Zhao, Peikun; Li, Changlong; Lv, Jianyi; Liu, Xin; Du, Xiaoyan; Chen, Zhenwen
Abstract : Recent studies raise the possibility that eukaryotic translation elongation factor 1 alpha (eEF1A) may play a role in metabolism. One isoform, eEF1A2, is specifically expressed in skeletal muscle, heart and brain. It regulates translation elongation and signal transduction. Nonetheless, eEF1A2's function in skeletal muscle glucose metabolism remains unclear. In the present study, suppression subtractive hybridisation showed a decrease in Eef1a2 transcripts in the skeletal muscle of diabetic Mongolian gerbils. This was confirmed at mRNA and protein levels in hyperglycaemic gerbils, and in db/db and high-fat diet-fed mice. Further, this downregulation was independent of Eef1a2 promoter methylation. Interestingly, adeno-associated virus-mediated eEF1A2 overexpression in skeletal muscle aggravated fasting hyperglycaemia, hyperinsulinaemia and glucose intolerance in male diabetic gerbils but not in female gerbil models. The overexpression of eEF1A2 in skeletal muscle also resulted in promoted serum glucose levels and insulin resistance in male db/db mice. Up- and downregulation of eEF1A2 by lentiviral vector transfection confirmed its inhibitory effect on insulin-stimulated glucose uptake and signalling transduction in C2C12 myotubes with palmitate (PA)-induced insulin resistance. Furthermore, eEF1A2 bound PKCβ and increased its activation in the cytoplasm, whereas suppression of PKCβ by an inhibitor attenuated eEF1A2-mediated impairment of insulin sensitivity in insulin-resistant myotubes. Endoplasmic reticulum (ER) stress was elevated by eEF1A2, whereas suppression of ER stress or JNK partially restored insulin sensitivity in PA-treated myotubes. Additionally, eEF1A2 inhibited lipogenesis and lipid utilisation in insulin-resistant skeletal muscle. Collectively, we demonstrated that eEF1A2 exacerbates insulin resistance in male murine skeletal muscle via PKCβ and ER stress.